Between shades of gray - Sepetys, Ruta (Philomel Books, 2011)
In 1941, fifteen-year-old Lina, her mother, and brother are pulled from their Lithuanian home by Soviet guards and sent to Siberia, where her father is sentenced to death in a prison camp while she fights for her life, vowing to honor her family and the thousands like hers by burying her story in a jar on Lithuanian soil. Based on the author's family, includes a historical note.